2017
DOI: 10.24059/olj.v21i3.1237
|View full text |Cite
|
Sign up to set email alerts
|

Improving Digital Library Experiences and Support with Online Research Guides

Abstract: With a goal of improving the development and delivery of effective online information literacy resources, the purpose of this study was to look at how program level and the timing of the introduction of a Literature Review library guide within the program influenced online business student perceived value of the resource. A population of undergraduate business students (N=355) and online MBA students (N=319) were introduced to a Literature Review library guide during specific points in their programs. Students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, Brewer and Grondin (2017) reported that, following the completion of their initial research, the University Library has begun developing library guides that are embedded in the first six courses taken by all undergraduate students. The incorporation of the guides into the curriculum should increase the use of the guides and the associated library resources.…”
Section: Vol 16 No2 Juni-desember 2021 Issn 1978-9637 E-issn 2745-6390mentioning
confidence: 99%
“…Furthermore, Brewer and Grondin (2017) reported that, following the completion of their initial research, the University Library has begun developing library guides that are embedded in the first six courses taken by all undergraduate students. The incorporation of the guides into the curriculum should increase the use of the guides and the associated library resources.…”
Section: Vol 16 No2 Juni-desember 2021 Issn 1978-9637 E-issn 2745-6390mentioning
confidence: 99%
“…While tangible resources such as the print collection, and services such as reference and instructional services continue to feature significantly in conventional education in universities, the emergence of new service models (Ahenkorah-Marfo & Nikoi, 2019), such as ICT-enabled distance education, require more than tangible resources and the scope-limited traditional reference (Luo & Buer, 2015). Distance education subscribers require, in addition to library physical content, the provision of digital learning objects such as online tutorials, subject guides and open educational resources (Brewer, Rick, & Grondin, 2017;Courtney & Wilhoite-Mathews, 2015;Davis, Cochran, Fagerheim, & Thoms, 2016;Salem Jr, 2017) with an ultimate goal of producing information literate graduates (Fernández-Ramos, 2019;Ukwoma, Iwundu, & Iwundu, 2016).…”
Section: Introductionmentioning
confidence: 99%